THE EFFECT OF WORK-LIFE BALANCE AND WORK FATIGUE ON WITHDRAWAL BEHAVIOR IN WORK AMONG GEN Z IN JAKARTA WITH JOB SATISFACTION AS A MEDIATION VARIABLE - Vania Fredline Artanti; Hery Winoto TJ (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Changes in the dynamics of the workplace encourage the emergence of quiet quitting behavior , especially among Generation Z employees who are concerned about work-life balance and psychological well-being. This study aims to analyze the influence of work-life balance and burnout on job withdrawal behavior with job satisfaction as a mediating variable in Generation Z employees in Jakarta. The study used a quantitative approach with 120 respondents and was analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that work-life balance significantly influenced withdrawal behavior and job satisfaction, while burnout significantly influenced withdrawal behavior but not job satisfaction. Job satisfaction also significantly influenced withdrawal behavior and was able to mediate the influence of work-life balance on that behavior, but did not mediate the influence of burnout . These findings indicate the importance of improving work-life balance in strengthening the satisfaction and engagement of Generation Z employees and reducing the tendency of quiet quitting . Keywords: work-life balance , burnout , job satisfaction, quiet quitting , Generation Z.